2023
DOI: 10.3389/fimmu.2023.1145450
|View full text |Cite
|
Sign up to set email alerts
|

Predicting prognosis, immunotherapy and distinguishing cold and hot tumors in clear cell renal cell carcinoma based on anoikis-related lncRNAs

Abstract: BackgroundClear cell renal cell carcinoma (ccRCC) is the most frequently occurring malignant tumor within the kidney cancer subtype. It has low sensitivity to traditional radiotherapy and chemotherapy, the optimal treatment for localized ccRCC has been surgical resection, but even with complete resection the tumor will be eventually developed into metastatic disease in up to 40% of localized ccRCC. For this reason, it is crucial to find early diagnostic and treatment markers for ccRCC.MethodsWe obtained anoiki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Anoikis is a special type of programmed cell death that occurs when normal epithelial cells lose their connection with the extracellular matrix. This process helps eliminate misaligned or displaced cells, preventing the possibility of malignant tissue proliferation and influencing cancer development [35]. The study found that anoikis in fact can be adjusted by oxidative stress.…”
Section: Discussionmentioning
confidence: 91%
“…Anoikis is a special type of programmed cell death that occurs when normal epithelial cells lose their connection with the extracellular matrix. This process helps eliminate misaligned or displaced cells, preventing the possibility of malignant tissue proliferation and influencing cancer development [35]. The study found that anoikis in fact can be adjusted by oxidative stress.…”
Section: Discussionmentioning
confidence: 91%
“…Compared with hematological cancers, which are effectively targeted in many cases by chimeric antigen receptor (CAR) T cells, treatment of solid tumors with CAR-T therapy owing to vascular remodeling, hypoxia, and acidosis is often less effective ( 7 , 57 , 80 , 120 , 129 , 177 ). Given the constant trafficking of monocytes into tumors, macrophage-based cell therapies may constitute a feasible alternative to overcome obstacles to treat solid tumors, associated with the use of CAR T cells ( 15 , 57 , 80 , 120 , 129 , 177 ). Thus, engineering macrophages to deliver cytokines or nanoparticles to the TME or equipping them with specific receptors may be a promising therapeutic approach.…”
Section: Tam-targeted Therapiesmentioning
confidence: 99%
“…Hot tumors are attributed to infiltration of TMEs mostly by T cells ( 15 17 ). They intensify the immune response, engaging it to recognize and attack tumor cells and produce a good response to immunotherapy, including that with immune checkpoint inhibitors ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of reports have pointed out the influence of anoikis-related genes or lncRNAs on immune infiltrating microenvironment [ 30 , 31 ]. However, the mechanism has not been reported in depth.…”
Section: Introductionmentioning
confidence: 99%